Immune cell single-cell RNA sequencing analyses link an age-associated T cell subset to symptomatic benign prostatic hyperplasia - Broman, Meaghan M.; Lanman, Nadia A.; Vickman, Renee E.; Cresswell, Gregory M.; Kothandaraman, Harish; Kolliegbo, Andree; Paez, Juan Sebastian Paez; Glaser, Alexander P.; Helfand, Brian T.; Henry, Gervaise; Strand, Douglas W.; Franco, Omar E.; et al. (Frontiers in Immunology, 2025)
IntroductionBenign prostatic hyperplasia (BPH) is among the most common age-associated diseases in men. Prostatic immune cell infiltration is frequently observed with aging coincident with BPH; however, the contribution of age-related changes in immune cells to BPH is not clear. As T cells are the predominate immune cell in aged prostates, it is hypothesized that age-associated alterations in T cell subsets contribute to BPH symptoms.MethodsscRNA-seq data from immune cells isolated from small (≤40g) and large (≥90g) prostates from aged men (>50 years) were combined with previously published scRNA-seq data from three young organ donor prostates to compare young to aged prostate T cells and small to large aged prostate T cells. Cycling and senescent BPH patient-derived fibroblasts were treated with granzyme K and senescence-associated secretory phenotype (SASP)-associated cytokines were measured by ELISA.ResultsAn age-associated CD8+ T cell subset (Taa) with high Granzyme K (GZMKhi) and low Granzyme B (GZMBlow) gene expression infiltrated aged human prostates and positively correlated with International Prostate Symptom Score (IPSS). A velocity analysis indicated that CD8+ T cell differentiation is altered in large BPH prostates compared to small age-matched prostates, favoring Taa accumulation. In vitro granzyme K treatment of human BPH patient-derived large prostate fibroblasts increased secretion of pro-inflammatory senescence-associated secretory phenotype (SASP)-associated cytokines.DiscussionThese data suggest that granzyme K-mediated stimulation of prostate stromal fibroblast SASP cytokine and chemokine production promotes prostate immune cell recruitment and activation. Overall, these results connect symptomatic BPH with immune aging.